Maximum Acceleration Based on Probabilistic Seismic Hazard Analysis at Koni Mamuju Building Mamuju, West Sulawesi - Asriadi Owen; K. A Hanindya; Mayga Bima (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2026)
This study aims to analyze the potential for seismic hazards in the Mamuju area, West Sulawesi using the Probabilistic Seismic Hazard Analysis (PSHA) approach. Using historical earthquake data obtained from the USGS earthquake catalog and EZ-FRISK software, this study assesses the potential for maximum ground acceleration (PGA) and the risk of liquefaction that can damage buildings. This study also developed calculations using deterministic and probabilistic methods to model earthquake soil movements that affect the Koni building at the research location. The analysis of the results obtained showed an increase in soil acceleration on the ground surface, with significant potential damage due to earthquake waves, especially in sandy soils that are susceptible to liquefaction. This study suggests the need for earthquake-resistant building designs that are adapted to local geological characteristics to reduce the risk of earthquake damage. Using the results of the PSHA analysis, this study provides important insights into earthquake hazard mitigation in the Mamuju area which still lacks seismic research.